PENGARUH INTENSIFITAS PEMBERIAN KREDIT DAN TINGKAT NON PERFORMING LOAN TERHADAP TINGKAT PROFITABILITAS PADA PT. BANK PERKREDITAN RAKYAT BALE ENDAH RAHAYU - Aditya Achmad Fathony; Elin Kodariah (AKURAT | Jurnal Ilmiah Akuntansi FE UNIBBA, 2016)
In this study, the authors take the title "Influence intensivity Lending And The level of Non Performing Loan To Profitability". The aim of this study was to determine how much influence intensivity provision of credit and the level of non-performing loans on the level of profitability in PT.BPR BALE ENDAH RAHAYU period 2009-2014. The method used in this research is descriptive and verification method with quantitative approach. Intensivity to know the magnitude of the effect of credit and the level of non-performing loans to profitability by using statistical tests. Statistics used were multiple linear regression analysis, Classical Assumption Test, the coefficient of determination by using SPSS 22.0 for Windows to compare the calculations manually. Based on test results with manual processing or by SPSS, the result is that simultaneous correlation between intensivity Lending and level of non-performing loans on the level of profitability is to have a very strong relationship and direction. F Based on the test, whether ???? ???????????????????? or ???? hitung obtained results that intensivity Lending and level of nonperforming loans simultaneously significant effect on the level of profitability in PT.BPR Baleendah Rahayu Bandung. These results indicated also by the determination coefficient of 87.1%, while the remaining 12.9% is influenced by other factors such as the level of Bank Liquidity, Cash Turnover, Turnover Debt, Capital Structure, Cost Of Fund and others